(untitled) (Lantanida Journal, 2017)
This research was conducted to develop a worksheet learners (LKPD) scientific approach based on the concept of buffer solution. LKPD validated by experts and tested on students. The purpose of this study was to see the results of learning, activity and response learners. The study was conducted in SMA 11 Banda Aceh by using quantitative research methods reasearch research and development (R&D). This study used a quasi-experimental design with pre-test and post-test Group. The average score of the expert assessment of 3.28 (good). LKPD trial results showed that 95.31% of teachers and 97.5% of students responded positively to LKPD. Normality and homogeneity test results show that the data homogeneous and normal distribution. T-test results obtained tarithmetic>ttable (4.58>2.072) which means there is a significant difference in learning outcomes between the two classes. Activities learners also showed a difference in the experimental class showed better activity than the control class. Learners also give a positive response to the use of LKPD, so it can be concluded that learning by using LKPD-based scientific approaches to improve learning outcomes and learner activity.